IMMUNOPATHOGENETIC ASPECTS OF ISCHEMIC STROKE - E. R. Chernykh (SPb RAACI, 2018)
Immune system plays a key role in pathogenesis of ischemic stroke. Ischemic brain injury causes destruction of cells and extracellular matrix proteins, and the release of „danger“ molecules that cause rapid activation of innate immunity, and induce adaptive autoimmune reactions. The cells of innate immunity are responsible for elimination of cellular and extracellular debris and tissue repair, being, however, involved in post-ischemic inflammation causing brain injury. An adaptive immune response which develops within a few days is directed against self-antigens, being not related to nervous tissue damage in acute phase of stroke. The cells of adaptive immunity are able to regulate microglial activity and promote repair processes in the central nervous system. However, long-term persistence of lymphocytes with reactivity for brain-derived antigens may be involved into the atrophy of cerebral cortex, and development of dementia in remote post-stroke period. Immune response following ischemic brain stroke is manifesting by local and systemic reactions. Nevertheless, in contrast to prolonged local intracerebral inflammation in infarction area, and peri-infarction region, a systemic inflammatory response is quickly replaced by development of immunosuppression, as evidenced by lymphopenia, lymphoid organ atrophy and defective functions of immune cells. Immunosuppression is largely due to activation of sympathoadrenal system, aiming for limitation of inflammatory and autoimmune reactions. However, excessive immunosuppression leads to development of infectious complications, which may often cause lethal outcomes, and also may have a negative impact on efficiency of repair processes. The present review provides experimental and clinical data describing the innate and adaptive immune reactions in response to cerebral ischemia. Moreover, this review discusses possible pathogenetic importance of immune cells and their positive or negative effects, thus allowing further development of new therapeutic approaches for treatment of ischemic stroke.